PMO-193 Outcome of non-compliance with a programme of variceal sclerotherapy in a DGH. (28th May 2012) - Jahanshad, A; Hanson, P
Abstract : Introduction: Bleeding from oesophageal varices is a serious medical emergency which can be prevented by endoscopic variceal ligation either as primary or secondary prophylaxis. We aimed to establish the degree of compliance with scheduled endoscopic therapy, the reasons for non-compliance and the clinical consequences. Methods: We examined the medical notes and endoscopy reports of 50 cirrhotic patients with oesophageal varices who underwent endoscopic band ligation at the Great Western Hospital over the last 3 years. We categorised the patients into two groups: those whose were followed up in accordance with BSG guidelines on the scheduling of oesophageal sclerotherapy and those whose follow-up fell short of these standards. We assessed the incidence of variceal haemorrhage in the two groups and investigated the reasons of inappropriate follow-up. Results: 50 patients underwent 229 endoscopy procedures for varices during the 3-year period. Of these, 45 endoscopies were performed outside the recommended time schedule: 25 were booked incorrectly; 12 were booked correctly but experienced a delay; 8 were both booked incorrectly and further delayed. 20 patients died (none from haemorrhage). Of the 18 out of 50 patients who were followed up appropriately none experienced re-bleeding. Among the group who were non-compliant with the recommended scheduled for whatever reason (45 delayed procedures in 32 patients) three patients underwent five admissions for GI bleeding during follow-up. Secondary prophylaxis after a first variceal haemorrhage was performed in 18 patients of who 9 were non-compliant with guidelines; 6 of these were due to non-attendance and 3 due to delays in booking due to pressure on appointments. Conclusion: There is a clear difference in outcomes between those whose variceal bleed is followed up in a timely way with repeat endoscopy as per BSG guidelines and those who, for whatever reason, are non-compliant with the guidelines. Emphasis must be placed on correct booking procedures and efforts made to contact patients about imminent appointments to minimise morbidity and mortality from variceal rebleeding. Competing interests: None declared.